Corporate Social Responsibility in Limited Liability Companies in National Mining Law - Febiola, Cahya Putri; Susanti, Susi; Pratiwi, Charine Alya; Rumelawanto, Fajar Putra Prastina (Journal of Law and Policy Transformation, 2024)
Corporate Social Responsibility (CSR) is a social and environmental responsibility that must be implemented by companies in the natural resources sector, including mining, in accordance with Law Number 40 of 2007. This research aims to analyze CSR regulations in Indonesia, especially in the mining industry, and evaluate CSR regulations in the Limited Liability Company Law and Mineral and Coal Law and their derivative regulations. This research also highlights provisions regarding reclamation, post-mining activities, and community empowerment as a form of CSR in the Minerba Law. Using the normative analysis method, it was found that there was a regulatory gap between Minerba Law with PP 78/2010 related to occupational health, which is an important part of social responsibility. Therefore, the implementation of CSR in the mining sector still faces challenges, especially in ensuring that mining companies carry out their obligations consistently. This research recommends harmonization of regulations to strengthen legal certainty and ensure companies implement CSR in a sustainable manner to achieve environmentally sound development and social welfare.